Immunobiological mechanisms of stimulation of the body's natural resistance in conditions of altered reactivity. (December 2019) - Trukhachev, V; Agarkov, A; Dmitriev, A; Ermakov, A; Agarkov, N; Shulunova, A; Sidelnikov, A; Malysheva, L
Abstract: The paper studied the effect of microbial polysaccharides on the leukogram of laboratory animals and studied the dynamics of peripheral blood parameters with an assessment of immunobiological reactivity based on established patterns of physiological status. The results of numerous studies of the state of natural resistance of farm animals indicate that protective forces are a dynamic indicator, and is determined both by the genetic characteristics of the body and the impact of various environmental factors. This circumstance allows directionally influencing the formation and manifestation of the body's defenses. Thus, the study of the immunological reactivity of the organism of farm animals becomes relevant for understanding the pathogenesis of diseases, for rational pathogenetic therapy. The problem of increasing the nonspecific resistance of productive animals has not lost its relevance in the current difficult economic situation in Russia. This fact is dangerous by the manifestation of enzootic outbreaks of infectious diseases and a gradual decrease in the breeding value of animals.